Antiangiogenic VEGF Isoform in Inflammatory Myopathies - Nila Volpi; Alessandra Pecorelli; Paola Lorenzoni; Francesco Di Lazzaro; Giuseppe Belmonte; Margherita Aglianò; Luca Cantarini; Fabio Giannini; Giovanni Grasso; Giuseppe Valacchi (Mediators of Inflammation)
Objective. To investigate expression of vascular endothelial growth factor (VEGF) antiangiogenic isoform A-165b on human muscle in idiopathic inflammatory myopathies (IIM) and to compare distribution of angiogenic/antiangiogenic VEGFs, as isoforms shifts are described in other autoimmune disorders. Subjects and Methods. We analyzed VEGF-A165b and VEGF-A by western blot and immunohistochemistry on skeletal muscle biopsies from 21 patients affected with IIM (polymyositis, dermatomyositis, and inclusion body myositis) and 6 control muscle samples. TGF-β, a prominent VEGF inductor, was analogously evaluated. Intergroup differences of western blot bands density were statistically examined. Endomysial vascularization, inflammatory score, and muscle regeneration, as pathological parameters of IIM, were quantitatively determined and their levels were confronted with VEGF expression. Results. VEGF-A165b was significantly upregulated in IIM, as well as TGF-β. VEGF-A was diffusely expressed on unaffected myofibers, whereas regenerating/atrophic myofibres strongly reacted for both VEGF-A isoforms. Most inflammatory cells and endomysial vessels expressed both isoforms. VEGF-A165b levels were in positive correlation to inflammatory score, endomysial vascularization, and TGF-β. Conclusions. Our findings indicate skeletal muscle expression of antiangiogenic VEGF-A165b and preferential upregulation in IIM, suggesting that modulation of VEGF-A isoforms may occur in myositides.